Diverging perceptions of therapeutic effectiveness in complementary and alternative medicine: A cross-sectional study among oncology patients and healthcare professionals - Ljerka , Armano; Vanja, Vasiljev; Tomislav, Rukavina; Trnčević, Martina; Filipčić, Igor; Aleksandar, Racz (Edelweiss Applied Science and Technology, 2025)
Complementary and alternative medicine (CAM) is increasingly used by cancer patients worldwide, often as a supplement to conventional treatment. While specific CAM modalities, such as herbal medicine and massage, are gradually gaining empirical support, many remain controversial within a biomedical context. Nevertheless, the perception of CAM effectiveness by patients and healthcare professionals has been rarely studied comparatively, especially in oncology. A cross-sectional study was conducted at Sestre Milosrdnice University Hospital in Zagreb, Croatia, involving 832 participants: 411 oncology patients and 421 healthcare workers, including 100 physicians and 321 nurses. A structured, stratified questionnaire based on adapted versions of the CAM Health Belief Questionnaire (CHBQ) and the Integrative Medicine Attitude Questionnaire (IMAQ) was used to gather data. Statistical analyses included descriptive statistics, analysis of variance (ANOVA), and Tukey's post hoc tests. Patients consistently showed a more positive attitude towards the effectiveness of CAM compared to physicians, with nurses falling in between the two groups. Herbal medicine and massage therapy were found to be the most effective among all groups. In contrast, spiritual and energy-based practices (e.g., Reiki, spiritual healing, bioenergy) showed the greatest differences. Statistically significant differences (p < 0.001) were observed between physicians and the other two groups for almost all modalities. The level of familiarity also varied considerably, with patients reporting significantly less familiarity with various techniques. The study reveals a marked discrepancy between patients and healthcare providers in their perceptions of the effectiveness of alternative treatments, reflecting broader epistemological and cultural differences. These findings have important implications for patient-provider communication, integrative oncology, and medical education. Addressing these gaps requires not only scientific expertise but also cultural sensitivity and ethical commitment. CAM perceptions should not be dismissed as irrational; instead, they should be explored as meaningful expressions of patients' agency, hope, and their existential coping mechanisms.